Unraveling the Nature of Sites Active toward Hydrogen Peroxide Reduction in Fe-N-C Catalysts - Choi, Chang Hyuck; Choi, Won Seok; Kasian, Olga; Mechler, Anna K.; Sougrati, Moulay Tahar; Bruller, Sebastian; Strickland, Kara; Jia, Qingying; Mukerjee, Sanjeev; Mayrhofer, Karl; Jaouen, Frederic (Angewandte Chemie International Edition, 2017)
Fe-N-C catalysts with high O-2 reduction performance are crucial for displacing Pt in low-temperature fuel cells. However, insufficient understanding of which reaction steps are catalyzed by what sites limits their progress. The nature of sites were investigated that are active toward H2O2 reduction, a key intermediate during indirect O-2 reduction and a source of deactivation in fuel cells. Catalysts comprising different relative contents of FeNxCy moieties and Fe particles encapsulated in N-doped carbon layers (0-100%) show that both types of sites are active, although moderately, toward H2O2 reduction. In contrast, N-doped carbons free of Fe and Fe particles exposed to the electrolyte are inactive. When catalyzing the ORR, FeNxCy moieties are more selective than Fe particles encapsulated in N-doped carbon. These novel insights offer rational approaches for more selective and therefore more durable Fe-N-C catalysts.
Keywords: fuel cells; heterogeneous catalysis; hydrogen peroxide; iron; oxygen reduction reaction